Activated magnetic lipase-inorganic hybrid nanoflowers: A highly active and recyclable nanobiocatalyst for biodiesel production. (June 2021) - Zhong, Le; Jiao, Xiaobo; Hu, Hongtong; Shen, Xuejian; Zhao, Juan; Feng, Yuxiao; Li, Conghai; Du, Yingjie; Cui, Jiandong; Jia, Shiru
Abstract: In this study, the surfactant activated lipase from Aspergillus oryzae was used to prepare magnetic hybrid nanoflowers by embedding Fe3 O4 magnetic nanoparticles (MNPs) into hybrid nanoflowers (MhNF). Meanwhile, MNPs were integrated into the activated lipase hybrid nanoflowers through covalent cross-linking (cross-linked-MhNF). Activity recovery of the MhNF and cross-linked-MhNF was 190% and 174%, respectively. However, activity recovery of lipase hybrid nanoflowers (hNF) only retained 77%. Furthermore, the MhNF displayed higher K cat /K m value than free lipase, indicating high catalytic efficiency of MhNF. Compared with free lipase, the MhNF exhibited high tolerance against methanol and storage stability. Furthermore, the MhNF could be easily recycled by magnet without obvious activity loss. After reusing for 10 cycles, the activated hNF only retained 26% activity of its original activity, while the MhNF still maintained 84% activity of its initial activity, indicating excellent reusability. In the reaction of producing biodiesel from soybean oil, the MhNF-catalyzed biodiesel yield reached 88%, while the free enzyme was only 69%. The yield of biodiesel catalyzed by MhNF was maintained at 76% even after 6 consecutive cycles. Graphical abstract: Image 1 Highlights: Activated magnetic lipase-inorganic hybrid nanoflowers (MhNF) were successfully synthesized. Fe3 O4 nanoparticles were successfully integrated into the activated lipase hybrid nanoflowers with surfactants. The MhNF exhibited higher activity, immobilization efficiency, and stability than free lipase. The MhNF could be effectively used in the production of biodiesel from soybean oil.